Intertextuality in Tragedy and Crime Fiction in Shakespeare’s Othello, Webster’s the Duchess of Malfi, Christie’s Curtain and Sleeping Murder - الدباغ، تارا طاهر سليمان (جامعة بغداد - كلية الآداب, 2019)
Christie maneuvers the storylines of Shakespeare’s Othello (c. 1604) and Webster's The Duchess of Malfi (1613/14) into crime fiction in, respectively, Curtain (1975) and Sleeping Murder (1976), establishing the actions of certain characters as patterns of behavior. Yet, despite the similarities in the four texts, and in accordance with the requirements of her genre, she does not allow the resulting structuralist intertextuality diminish the suspense in her stories. Unlike the tragedies which aim at emotional involvement, her two books encourage a mental endeavor to solve the puzzle of the crimes.
تناور كرستي قصتي مسرحيتي "عطيل" (1604) لشكسبير و"دوقة مالفي" (1613/14) لويبستر في روايتيها البوليسيتين "ستارة" (1975) و "الجريمة النائمة" (1976) على التوالي، مرسخة بذلك تصرف بعض الشخصيات في هذه الأعمال كأنماط سلوكية. ولكن، وبالرغم من التشابه في هذه النصوص الأربعة، وتوافقا مع متطلبات صنفها الأدبي، فإن كرستي لا تدع التناص البنيوي الناتج أن يقلل أو يضعف التشويق في روايتيها. خلافا للمسرحيتين المأساويتين اللتين تهدفان إلى اكتناف عاطفي لجمهور المشاهدين، فإن روايتي كرستي تحثان القارئ على محاولات وسعي ذهني لحل ألغاز الجرائم المرتكبة فيها.
Keywords: الرواية البوليسية -- التناص البنيوى -- المسرحيات الأدبية -- النقد الأدبى